Art of deception : mereka menipu dunia : Amerika, freemason, Zionis - Gray, Jerry D. [ (Jerry Duane)] , 1960- (PTS Islamika, 2012)
Truth finally revealed as well. That there is a group of people going to realize the power of the devil with the Antichrist at its head. For those who like conspiracy theories, I suggest you to read